1995
DOI: 10.1152/jappl.1995.78.5.1882
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spaceflight, hindlimb suspension, and venous occlusion on alpha 1-adrenoceptors in rat vena cava

Abstract: Effects of hindlimb suspension, spaceflight, and venous occlusion were examined in isolated strips from rat vena cava by using both [3H]prazosin-binding and contraction responses evoked by norepinephrine. Sensitivity to norepinephrine was decreased without modification of the maximal contractile response. Furthermore, the high K(+)-induced contractions were not affected, suggesting that there was no interference with voltage-dependent Ca2+ channels. The sensitivity of the norepinephrine-induced contraction to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
2
18
3
Order By: Relevance
“…Purdy et al (1998) reported no significant effect of rat hindlimb suspension on maximal vein response to noradrenaline (jugular and femoral). However, Sayet et al (1995) revealed modifications in the properties of rat vena cava. Alterations to noradrenaline‐induced contraction by decreased affinity to α 1B adrenoreceptors was observed after hindlimb suspension.…”
Section: Discussionmentioning
confidence: 98%
“…Purdy et al (1998) reported no significant effect of rat hindlimb suspension on maximal vein response to noradrenaline (jugular and femoral). However, Sayet et al (1995) revealed modifications in the properties of rat vena cava. Alterations to noradrenaline‐induced contraction by decreased affinity to α 1B adrenoreceptors was observed after hindlimb suspension.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous investigators (6,25,27) have used the HU model to simulate cardiovascular deconditioning in rats. A study by Murison (23) argued that the effects of HU are not a result of an increase in stress due to HU treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence for reduced vascular responsiveness has come from animal studies using real and simulated microgravity. Sayette and co-workers (27) found that the sensitivity of the vena cava to norepinephrine (NE) was reduced in rats exposed to microgravity during spaceflight or simulated microgravity in the form of hindlimb unweighting (HU). Delp and co-workers (5,6) found that the maximal contractile response of the isolated rat aorta to several vasoconstrictor agents was reduced by HU.…”
Section: Rats; Blood Vessels; Norepinephrine; In Vivomentioning
confidence: 99%
“…These results are consistent with a previous observation of diminished ␣-receptor density in the vena cava of rats following spaceflight (59) as a potential mechanism for the diminished venoconstriction. Several studies using HU rats have likewise reported a decreased venoconstriction to NE in the vena cava and mesenteric veins (13,18,59,60), but not in jugular and femoral veins (46). Similar to mesenteric arteries, another potential mechanism for spaceflight-associated impairment of venoconstriction is a blunting of intracellular Ca 2ϩ release through the down-regulation of ryanodine receptors (61 The primary unanswered question regarding vascular alterations associated with spaceflight is the stimulus for the change.…”
Section: Mechanistic Basis For Diminished Venous Constrictionmentioning
confidence: 99%